Landscape Painting Around the Generation of ‘27 - Jiménez-Alcalá, Benito (Arte, Individuo y Sociedad, 2022)
The Generation of ’27 changed radically precedent thinking and aesthetics. Although outstanding by poetic production, its influence and innovative character would involve the rest of arts. Heir to the 98’ painting, the landscaping topic reinvented adding new meanings associated to the folk, the spontaneous, primitivism and lyricism, denying any nationalistic or custom trace. The School of Vallecas embodied this transformation, defining a personal landscape model that would gather the creative movements at that time. The exploration of the Castilian desolated agrolands through a language closed to abstraction allowed the artistic definition of an essential, sentimental and subliminal nature. It would converge with surrealism, when trying to go beyond reality and connecting with more profound and oneiric emotions. The landscape reinvention that took place around the School would project its influence on the following decades, even after the Spanish Civil War, unlike the rest of Europe, where nature representations were definitively relegated. This article tries to enquire about the origins, incentives and significances of this new landscaping.